The management of asymptomatic congenital pulmonary airway malformation: results of a European Delphi survey - Kersten, Casper M.; Hermelijn, Sergei M.; Mullassery, Dhanya; Muthialu, Nagarajan; Cobanoglu, Nazan; Gartner, Silvia; Bagolan, Pietro; Mesas Burgos, Carmen; Sgrò, Alberto; Heyman, Stijn; Till, Holger; Suominen, Janne; et al. (Children, 2022)
Consensus on the optimal management of asymptomatic congenital pulmonary airway malformation (CPAM) is lacking, and comparison between studies remains difficult due to a large variety in outcome measures. We aimed to define a core outcome set (COS) for pediatric patients with an asymptomatic CPAM. An online, three-round Delphi survey was conducted in two stakeholder groups of specialized caregivers (surgeons and non-surgeons) in various European centers. Proposed outcome parameters were scored according to level of importance, and the final COS was established through consensus. A total of 55 participants (33 surgeons, 22 non-surgeons) from 28 centers in 13 European countries completed the three rounds and rated 43 outcome parameters. The final COS comprises seven outcome parameters: respiratory insufficiency, surgical complications, mass effect/mediastinal shift (at three time-points) and multifocal disease (at two time-points). The seven outcome parameters included in the final COS reflect the diversity in priorities among this large group of European participants. However, we recommend the incorporation of these outcome parameters in the design of future studies, as they describe measurable and validated outcomes as well as the accepted age at measurement.
Gesehen am 23.10.2023